Stages of International Virtual Competition Implementation in Indonesia - Dianita, Indria Angga; Adim, Adrio Kusmareza; Dirgantara, Pradipta; Kalaloi, Abdul Fadli; Ramdan, Andry Mochamad (Universitas Pendidikan Indonesia, 2024)
The purpose of this study was to explore and describe the stages of implementing virtual competition as one of the types of virtual events. The virtual competition which was being studied was the 2021 International Photography and Short Movie Festival (IPSMF). One of the industries most affected by the Covid-19 pandemic is the event industry. As an industry that generates revenue from crowds of visitors, most event organizers are turning their offline agenda into virtual events. These phenomena continue to rise during the post-pandemic days. This research was conducted using a qualitative descriptive method. The analysis in this study was carried out based on the stages of organizing virtual which consists of Pre-Plan, Plan, Accomplish, and Response and Engage. This study indicate that the implementation of the 2021 IPSMF virtual competition has several differences. These differences exist in all stages. Based on these differences, it can be concluded that the activities carried out in the implementation of virtual events can be adjusted to the conditions and needs of the virtual event in question. The implementation of virtual events has a very wide audience reach compared to conventional events. Event organizers are required to create a digital platform with up to date, accurate, and interactive content.